Low-dose aspirin in the prevention of preeclampsia in twin pregnancies: A real-world study - Zhou, Qiongjie; Zhao, Xingzhong; Xu, Jinghui; Xiong, Yu; Barrett, Jon F. R.; Zhao, Xing-Ming; Li, Xiaotian (Frontiers in Cardiovascular Medicine, 2023)
Background: The use of low-dose aspirin for women with twin pregnancy remains controversial. This study was to describe the frequency of preeclampsia and aspirin use in twin pregnancies in real practice. Methods: This retrospective cohort study based on real-world data was conducted in the Obstetrics and Gynecology Hospital of Fudan University during 2013-20. Women with twin pregnancies who received prenatal care before 20 weeks of gestational age were included. They were divided into using low-dose aspirin (LDA group) and the women not using aspirin group (N-LDA group). The primary outcome was the frequency of preeclampsia, and secondary outcomes included early-onset and preterm mild and severe preeclampsia. Results: A total of 2,946 women had twin pregnancies and 241 were excluded due to missing information. Of 2,705 eligible women, 291 (10.75%) were administered aspirin and the other 2,414 (89.25%) did not. The patients in the LDA group were significantly more likely to be older, have a higher rate of use of ART, a previous history of hypertension and have gestational diabetes (P<0.05). In LDA group, aspirin compliance≥50% was relatively low (14.43%, 42/291). Preeclampsia occurred in 106 of 291 participants (36.43%) in LDA group, as compared with 449 of 2,411 (18.62%) in N-LDA group (OR: 2.15, 95% CI: 1.62-2.82; P < 0.01). The association was confirmed (OR: 1.74 , 95% CI: 1.26-2.4; P < 0.01) in the 1:2 case-matched analysis. Higher odds of ratio in LDA group were demonstrated (aORs > 1, P < 0.01), except for early-onset and preterm mild preeclampsia (P > 0.05). This association was confirmed in subgroup analysis of methods of conception (aOR ≥ 1, P > 0.05). Conclusion: Aspirin prescription of 75 to 100 mg in twin pregnancies was associated with no significant reduction of preeclampsia, which may be due to poor compliance of aspirin used. Further randomized controlled or prospective cohort studies are required.